Research on Anti-Wear Properties of Nano-Lubricated High-Speed Rolling Bearings under Various Working Conditions - Junning Li; Xiaojie Tang (Tehnički Vjesnik, 2023)
Under high-speed and light-load conditions, rolling bearings often suffer from skid damage and wear. Nano-lubrication could inhibit the wear failure of mechanical parts. Therefore, in this manuscript, nano-lubrication technology is adopted to improve the anti-wear performance of rolling bearings. Nano-mixed oil with different particle sizes and concentrations of silica nanoparticles are prepared. Based on an improved rolling bearing test rig, the friction coefficient, wear depth, and real-time temperature rise under different operating conditions are studied, and the friction and anti-wear mechanisms of the nano-lubricated high-speed rolling bearings are obtained.The results show that the wear failure of the light-load rolling bearings decreased by using nano-lubricated mixture oil. There is no direct correlation between the friction coefficient and wear depth in the rolling bearings. Moreover, the use of nano-lubrication can effectively suppress the wear of rolling bearings, especially in the absence of sufficient oil.This study can provide an effective support for nano-lubrication and its application in anti-wear of rolling bearings.